Legal aspects in dealing with the consequences of immigration and integration on Latvian labour market. - Riņķe, Patrīcija (Riga Graduate School of Law, 2018)
This thesis considers the field of migration as the main subject of this study because during all times it has been a very topical issue raised in the society. It is a very wide and still open-to discussions topic. During the history of migration to nowadays, many people have considered it as a huge problem with all the afterwards arising problems concerning many areas, including economics, demography, political and social issues. Nevertheless, studies show that worldwide migrants have grown to comprise 3% of the whole world population. Thus, it is necessary to shed light on the consequences it causes for the society and economy. Therefore, the aim of this work is to analyse the consequences of migration on the labour market in Latvian and come up with recommendations how legislative frameworks could be improved in order to mitigate negative consequences caused by migration.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Migration; Baltic States